Avaliação da maturidade pulmonar de cordeiros nascidos a termo e prematuros pela análise citológica, Test de Clements e contagem de corpos lamelares do líquido amniótico - Souza, Natália Cristina de [UNESP] (2014)
The aim of this study was to determine pulmonary and fetal maturity of lambs by means of cytological tests using Nile Blue and Hematoxilin-Shorr staining, Clements' test and amniotic fluid lamellar body count. Amniotic fluid samples were collected from 24 sheep in order to evaluate pulmonary and fetal maturity of their 32 lambs, which were divided into three groups: Normal group included 10 lambs born at term, after 145 days of gestation; Caesarean group included 11 lambs delivered by caesarean section, after 138 days of gestation; and Caesarean+Dexamethasone group included 11 lambs born from sheep submitted to caesarean section, after 138 days of gestation, and dexamethasone 16 mg/animal (IM) administration two days prior to the surgical procedure.. A significant difference was observed between Normal and Caesarean+Dexametasone groups using Nile Blue staining. However, this technique was not effective. Hematoxilin-Shorr staining was reliable and it was possible to verify that the Normal group differed statistically from the group submitted to Caesarean+Dexamethasone. In Clements' test, aiming to observe the presence of surfactant, which is characterized by the formation of bubble rings, approximately 20% of animals in the Normal group presented pulmonary maturity. However, the Caesarean group showed the least amount of bubbles (9.1%). The Caesarean+Dexamethasone group showed higher percentage of animals with pulmonary maturity (36.4%) when compared to the Normal and Caesarean groups The lamellar bodies were then measured to verify their size, which varied between 0.019 and 0.590 micrometers